Efficient Removal of Volatile Organic Compounds by FAU-Type Zeolite Coatings - Mathieu Diboune; Habiba Nouali; Michel Soulard; Joël Patarin; Guillaume Rioland; Delphine Faye; T. Jean Daou (Molecules, 2020)
Silicone and pure organic binders were used to develop FAU-type zeolite coatings applied on pre-treated aluminum substrates by using a spraying method and then cured under specific conditions. The influence of the amount of binder on adhesion properties of zeolite coatings was first investigated to determine the optimum ratio between zeolite and binder. Zeolite coatings were then elaborated with a high zeolite content (between 70 and 80 wt.%) to ensure high adsorption capacities. The amount of binders involved in different zeolite coatings was sufficient to achieve interesting adhesion and cohesion properties. The accessibility of zeolite microporosity was studied by nitrogen adsorption-desorption measurements, which revealed a very small or no loss of the micropore volume for the optimized coatings. Volatile Organic Compounds (VOCs) adsorption measurements were carried out using n-hexane as probe molecule. FAU-type zeolite in powder form adsorbs 180 mg/ganhydrous zeolite, whereas the amounts of n-hexane adsorbed by zeolite coatings ranged from 131 to 175 mg/ganhydrous zeolite.